Prevalence of folate and vitamin B12 deficiency in Mexican children aged 1 to 6 years in a population-based survey Distribución de la prevalencia de deficiencia de folato y vitamina B12 en niños mexicanos de 1 a 6 años de edad. Encuesta con base poblacional - Lucía Cuevas-Nasu; Verónica Mundo-Rosas; Teresa Shamah-Levy; Ignacio Méndez-Gómez Humaran; Marco Antonio Ávila-Arcos; Ma. del Rosario Rebollar-Campos; Salvador Villalpando (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To describe the magnitude and distribution of folate and vitamin B12 deficiency in Mexican children. MATERIALS AND METHODS: Folate and vitamin B12 serum concentrations were measured in a probabilistic sample of 2 099 children. Adjusted prevalence, mean concentrations and relevant associations were calculated based on series of logistic and linear regression models. RESULTS: The overall prevalence of folate and vitamin B12 deficiency were 3.2% and 7.7%, respectively. The highest prevalence of folate was found in the 2-year-old (7.9%), and of vitamin B12 in the 1 year-old (9.1%) groups. Being a beneficiary of the fortified milk program Liconsa was protectively associated with serum folate (p=0.001) and daily Intake of milk with vitamin B12 (p=0.002) concentrations. CONCLUSIONS: We describe the magnitude of folate and vitamin B12 deficiencies in Mexican children. The deficiency of both vitamins in children under 2 years old is a moderate public health problem in Mexico. OBJETIVO: Describir la magnitud de la deficiencia de folato y vitamina B12 en niños mexicanos. MATERIAL Y MÉTODOS: Se midieron las concentraciones séricas de folatos y vitamina B12 en una muestra probabilística de 2 099 niños. Se calcularon prevalencias ajustadas, medias de las concentraciones y las asociaciones relevantes mediante una serie de modelos de regresiones logísticas y lineales. RESULTADOS: La prevalencia global de deficiencia de folatos y vitamina B12 fueron 3.2% y 7.7%, respectivamente. La prevalencia más alta de folatos se encontró en el grupo de 2 años (7.9%) y de la vitamina B12 en los de 1 año de edad (9.1%). Ser beneficiario del programa de leche fortificada Liconsa estuvo asociado de manera protectora con el folato serico (p=0.001) y la ingestión diaria de leche con la de vitamina B12 (p=0.002). CONCLUSIONES: La deficiencia de ambas vitaminas, en los niños menores de dos años, es un problema de salud pública de magnitud moderada en México.